Teenage pregnancy in rural Ethiopia : The case of Jima Arjo District, East Wallaga, Western Ethiopia: Teenage pregnancy in rural Ethiopia - Mereta, Zerfe; Mereta, Zerfe; Tilahun, Temesgen; Fantahun, Firehiwot; Oljira, Rut; Mosisa, Getahun (Ethiopian Journal of Reproductive Health, 2024)
ABSTRACT Background : Teenage pregnancy is a major public health concern in developing nations like Ethiopia. Many psychological, financial, and health problems are associated with it. Objective : To determine the magnitude and associated factors of teenage pregnancy among teenagers visiting public health facilities in Jima Arjo district, East wallaga, Western Ethiopia, 2022. Methods: A facility-based cross-sectional study was conducted on 421 teenage females(10 to 19 years) in Jima Arjo District from February 15 to May 30, 2022. Data were collected , cleaned and analayzed using Epidata version 3.1. Level of significance of association was determined at a P- value?<?0.05. Results: In this study, the magnitude of teenage pregnancy was 17.1%. Married participants, attending secondary school, no awareness on family planning, not living with parents, and having a sister with the history of teenage pregnancy were significantly associated with teenage pregnancy. Conclusion: This study found that the magnitude of teenage pregnancy was high. Key stakeholders should work on prevention of early marriage, raise awareness on family planning, and encourage females’ education. Keywords: magnitude, associated factors, teenage pregnancy, Jima Arjo, East Wallaga